Developmental toxicity of three hexabromocyclododecane diastereoisomers in embryos of the marine medaka Oryzias melastigma. Issue 1 (15th December 2015) - Hong, Haizheng; Shen, Rong; Liu, Wanxin; Li, Dongmei; Huang, Lingming; Shi, Dalin
Abstract: The composition of major hexabromocyclododecane (HBCD) diastereoisomers, i.e. α-, β-, and γ-HBCDs, in marine biota is different from that of the commercially available form (technical HBCD), which is used extensively for toxicological studies. To properly evaluate the impact of HBCDs, the embryos of Oryzias melastigma were used to examine the developmental toxicity of the individual diastereoisomers. Results showed that HBCD diastereoisomers at the environmentally realistic concentrations in the embryos induced malformation rate and heartbeat, and caused the appearance of apoptotic heart. In addition, α-, β-, and γ-HBCDs had similar potency to stimulate the generation of reactive oxygen species, consequently leading to apoptosis in O . melastigma embryos. The order of the developmental toxicity of α-, β-, and γ-HBCDs in O . melastigma embryos was different from that in zebrafish embryos studied previously, which highlighted the importance of using species from both fresh and salt water for toxicity assessment. Highlights: α-, β-, and γ-HBCDs induced malformation rate in O . melastigma embryos. α-, β-, and γ-HBCDs induced heart beat in O . melastigma embryos. α-, β-, and γ-HBCDs induced oxidative stress and apoptosis in O . melastigma embryos. α-, β-, and γ-HBCDs had similar developmental toxicity in O . melastigma embryos.